2015
DOI: 10.1016/j.ijhydene.2015.05.077
|View full text |Cite
|
Sign up to set email alerts
|

Capacity of pitting corroded pipes under hydrogen assisted cracking

Abstract: Pipe strength a b s t r a c tSteel pipes used in the oil and gas industry when subject to corrosion pitting may fail as a result of internal pressure and metal cracking influenced by hydrogen embrittlement. The progressive shape of the crack, including at the instant of failure, is predicted under increasing internal pressure. It is proposed that when hydrogen-assisted cracking (HAC) is involved the shape of the crack front may be estimated from a parallel numerical analyses in the absence of HAC. The theory f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…The application of dissimilar welded joints is present in the power generation, petrochemical and transformation industries [1][2][3][4][5] . In the oil and gas extraction system, mainly offshore, these joints are subjected to very unfavorable working conditions, both in terms of oxidation and embrittlement and high pressures [6][7][8][9] . These conditions have demanded the adoption of materials and manufactoring processes that allow better mechanical properties and a lower sensitivity to the presence of hydrogen 10,11 .…”
Section: Introductionmentioning
confidence: 99%
“…The application of dissimilar welded joints is present in the power generation, petrochemical and transformation industries [1][2][3][4][5] . In the oil and gas extraction system, mainly offshore, these joints are subjected to very unfavorable working conditions, both in terms of oxidation and embrittlement and high pressures [6][7][8][9] . These conditions have demanded the adoption of materials and manufactoring processes that allow better mechanical properties and a lower sensitivity to the presence of hydrogen 10,11 .…”
Section: Introductionmentioning
confidence: 99%
“…They might be caused by abnormal or accidental events including dropped objects, dragging anchors, fishing equipment, sinking vessels, mudslides and harsh environments such as extreme waves and currents (Bjørnøy et al 2000;DNV 2010;Abeele et al 2013;Ghaednia et al 2015b). Under these circumstances, prediction of the strength of a pipeline is a subject that has attracted the attention of many researchers such as Dyau and Kyriakides (1993), Lancaster and Palmer (1996a) (1996), Estekanchi and Vafai (1999), Bjørnøy et al (2000), Bruschi et al (2005), Vitali et al (2005), Vaziri and Estekanchi (2006), Bartolini et al (2014), Ghaednia et al (2015a), Ghaednia et al (2015b) and Rajabipour and Melchers (2015). Relevant research can not only clarify the inner mechanism of the pipeline structure failure, but also facilitates the decision-making in engineering practice when pipelines undergo structural damage.…”
Section: Introductionmentioning
confidence: 99%
“…However, in poorly compacted backfill such as clays and heterogeneous clay and calcareous loams, corrosion can be quite non-uniform. These different topographies have been observed after only a few (3-4) years' exposure [8] and also after many (12)(13)(14)(15)(16)(17) years' exposure [9,10]. Figure 1 shows two examples, taken from on-going studies, covering a wide variety of locations, different pipe manufacturers, different cast iron compositions and pipes of a range of ages, from around 50 years eservice before failure to more than 120 years [11].…”
Section: Introductionmentioning
confidence: 99%
“…To obtain an estimate of the likelihood of pipe wall cracking caused by corrosion pitting and corrosion perforation, a finite element modelling analysis was carried out for a range of conventional pipe sizes and associated pipe wall thicknesses. This showed that for a range of sizes of pitting typical of cast iron [12], fracture and cracking could occur only for very thin wall thicknesses, much thinner than conventional, or under very high water pressures, again much greater than typical for cast iron water mains. This demonstrated that the typical topographies shown in Figure 1, with limited sizes of localised corrosion, were very unlikely to lead to crack initiation.…”
Section: Introductionmentioning
confidence: 99%